Analisa Pengembangan Kurikulum Pendidikan Dasar Berbasis Religious Culture - Budi, Irwan Setia (ANWARUL, 2022)
The purpose of this study is to define curriculum development. The process of designing a curriculum determines educational goals. The main purpose of education is to improve one's knowledge, attitudes, and skills, but society no longer considers the religious component that is essential for education. In this study used a qualitative method with a literature review approach. Therefore, we must pay attention to this, because the development of an advanced society depends not only on cognitive understanding, but also on the qualities of faith and positive attitudes, which enable individuals to apply the knowledge they have acquired in a way that is approved by Allah. S.W.T. A curriculum based on religious culture needs to be developed to produce graduates who are oriented to Allah SWT in the application of the knowledge gained in social life.